Characterisation of turnip mosaic virus isolates reveals high genetic variability and occurrence of pathotype 1 in Brazil - Rodrigues L.K. (2021)
© 2021, Koninklijke Nederlandse Planteziektenkundige Vereniging.Turnip mosaic virus (TuMV) infects many plant species, being the only potyvirus able to infect brassicas. TuMV isolates have been classified into 12 pathotypes according to symptoms induced in lines of Brassica napus, and molecularly clustered into six lineages (basal-B, basal-BR, Asian-BR, world-B, Iranian and OMs). Despite being considered one of the most important viruses infecting brassicas worldwide, there is little information on this virus in the Neotropical region. Aiming to fill in this gap and advance knowledge on occurrence, genetic variability, and biological aspects of TuMV in Brazil, 40 isolates were identified and characterised. Five of these isolates were selected to determine their host range, sequence their genomes, and for phylogenetic, recombination and diversity analyses. Mechanical inoculations performed on plant species from 10 families showed differences in symptom expression among isolates. Inoculations of 13 TuMV isolates in B. napus lines revealed occurrence only of the pathotype 1. According to phylogenetic analyses of the coat protein, TuMV Brazilian isolates clustered into the groups: world-B (subgroups world-B2 and world-B3) and basal-BR. In the latter, there was a formation of a subclade named Brazilian subgroup composed by 31 Brazilian TuMV isolates. Intralineage and interlineage recombination events of world-B, basal-B and basal-BR suggest that Brazilian TuMV isolates had a European origin. Our diversity analysis suggest that a strong negative selection is acting on polyprotein coding region. We confirmed that Brazilian TuMV isolates showed high variability, which together with their ability to infect wild brassicas and to circumvent resistance genes highlight their genetic and epidemiological potential in causing damages in cultivated species of brassicas and other crops in Brazil.